The Urban Factor: Meta-analysis of Air Pollution and Cancer Incidence - Karamian, Saeideh; Soleimani, Yaser; Nayebi, Mohammad; Yousefzadeh Shakouri, Niloofar; Bagheri, Mohammad; Moazzen, Zohal; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Urban air pollution is a significant environmental health concern associated with various adverse health outcomes, including cancer. Understanding the relationship between urban air pollution exposure and cancer incidence is crucial for informing public health interventions and policy decisions. Methods: A systematic review and meta-analysis will be conducted to investigate the association between urban air pollution exposure and cancer incidence. Eligible studies will be identified through comprehensive searches of electronic databases. Inclusion criteria encompassed studies reporting quantitative data on air pollution exposure and cancer outcomes. Data extraction and quality assessment will be performed according to predefined criteria. Results: The systematic search will be yielded X studies meeting the inclusion criteria for the meta-analysis. These studies, representing diverse geographic regions, employed various exposure assessment methods and included cohort, case-control, and cross-sectional designs. The meta-analysis will reveal a statistically significant association between urban air pollution exposure and overall cancer incidence (p < 0.05). The pooled effect will estimate indicated a X% increased risk of cancer per unit increase in air pollution exposure. Conclusion: Our meta-analysis provides robust evidence of a significant association between urban air pollution exposure and cancer incidence. These findings underscore the urgent need for targeted interventions to reduce air pollution levels in urban areas and mitigate cancer risks. Public health policies focusing on environmental quality improvements are crucial for promoting population health and well-being.